Genetic parameters for growth and carcass traits from crossbreeding - Andries, K.M.; Schalles, R.R.; Franke, D.E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growth and carcass data from 5 years of a long-term, rotational, crossbreeding project were used to calculate heritabilities and genetic and phenotypic correlations for direct and maternal birth and weaning weight, gain on feed, hot carcass weight, ribeye area, marbling score, and age at slaughter. Angus, Brahman, Hereford, Charolais, Simmental, and Gelbvieh breeds were involved. Heritabilities of traits ranged from low (maternal weaning weight 0.04) to moderate (direct weaning weight 0.41). Direct birth weight, direct weaning weight, gain on feed, and hot carcass weight had moderate to high genetic correlations. Marbling had negative genetic correlations with birth and weaning weight but positive correlations with slaughter age and hot carcass weight.
Keywords: Beef; Breeds; Heritability; Correlations; Carcass traits; Growth